2014
DOI: 10.1371/journal.pone.0099055
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Imaging Endoscopy Equipped with Laser Light Source from Preclinical Live Animal Study to First-In-Human Subject Research

Abstract: A goal in next-generation endoscopy is to develop functional imaging techniques to open up new opportunities for cancer diagnosis. Although spatial and temporal information on hypoxia is crucial for understanding cancer physiology and expected to be useful for cancer diagnosis, existing techniques using fluorescent indicators have limitations due to low spatial resolution and invasive administration. To overcome these problems, we developed an imaging technology based on hemoglobin oxygen saturation in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…To overcome this, a technique employing a combination of wavelengths with an imaging system composed of two laser diodes and a color CCD sensor it is possible to produce an oxygen saturation map based on the difference in absorption of oxy-hemoglobin and deoxy-hemoglobin accounting for hematocrit. 64,65 A proof of concept study involving 40 cases (n = 40) with established malignancies of the pharynx, oesophagus and colon illustrated a significant difference in the oxygen saturation map between the neoplastic and non- neoplastic areas in the oesophagus and colon only. These preliminary findings of functional imaging may aid diagnosis, predict response to cancer therapies including the outcomes of clinical trials pending larger scale study.…”
Section: Neoplasiamentioning
confidence: 99%
“…To overcome this, a technique employing a combination of wavelengths with an imaging system composed of two laser diodes and a color CCD sensor it is possible to produce an oxygen saturation map based on the difference in absorption of oxy-hemoglobin and deoxy-hemoglobin accounting for hematocrit. 64,65 A proof of concept study involving 40 cases (n = 40) with established malignancies of the pharynx, oesophagus and colon illustrated a significant difference in the oxygen saturation map between the neoplastic and non- neoplastic areas in the oesophagus and colon only. These preliminary findings of functional imaging may aid diagnosis, predict response to cancer therapies including the outcomes of clinical trials pending larger scale study.…”
Section: Neoplasiamentioning
confidence: 99%
“…The glass capillary tube with an inside diameter of 1.15 mm is used to mimic the blood vessels and the intralipid strongly scattered incident light to simulate the living tissue around blood vessel [19]. Deoxyhemoglobin solutions were created by adding to every 5 mg of Sodium Dithionite per 1 ml of blood to achieve a sample with oxygen saturation of 0% [11].…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. 17, we reported on a clinical study of StO 2 imaging using a laser illumination endoscope system. The results showed that StO 2 imaging could clearly distinguish neoplasia from non-neoplasia in the esophagus and colorectum.…”
Section: Discussionmentioning
confidence: 99%
“…2, we developed a prototype endoscope system for gastroenterological endoscopy that allowed us to obtain StO 2 distribution images of tissue. As with the other types of our prototype systems, 17,28 the light source of the system provided four bands of light: two blue narrow bands at 450 and 470 nm, a green broad band, and a red band [ Fig. 1(c)].…”
Section: Development Of Sto 2 Imaging Endoscopementioning
confidence: 99%
See 1 more Smart Citation